DEVELOPMENT OF MATERIALS FOR IMMOBILIZATION OF CESIUM AND CERIUM BASED ON A COMBINATION OF NOCHAR SUPER ADSORBENT AND UNSATURATED POLYESTER FOR PRODUCTION WASTE RADIOISOTOPE 99Mo - Setiawan, Risdiyana; Sugita, Purwantiningsih; Farid, Muhammad; Ratiko; Aisyah; Rachmadetin, Jaka; Heriyanto, Kuat; Purwanto, Yuli; Saputra, Dwi Luhur Ibnu; Artiani, Pungky Ayu (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2025)
This research aims to develop unsaturated polyester-based materials combined with Nochar superabsorbent as radioactive waste immobilization materials. The focus is to lock up radioactive elements such as cesium (Cs) and cerium (Ce), which are used as surrogates for 99Moradioisotope waste. This study evaluates the performance of immobilized materials in adsorbing and stabilizing radioactive elements using various waste loading percentages of 10%, 15%, 20%, and 25%. The characterization results showed that the combination of unsaturated polyester and Nochar was able to absorb the waste effectively without any migration of radioactive elements to the environment, according to the leaching test results. However, based on the compressive strength test, a high increase in waste loading resulted in a decrease in the mechanical strength of the composite. Thus, an optimal waste loading of 20% provides a balance between absorption capacity and mechanical strength. This study demonstrates the potential of using unsaturated polyester and Nochar as safe and effective immobilization materials for radioactive waste, especially in the context of long-term radioactive waste management.